Assessment and training in home-based telerehabilitation of arm mobility impairment - Perry, Joel C.; Rodriguez de Pablo, Cristina; Balasubramanian, Sivakumar; Cavallaro, Francesca I.; Belloso, Aitor; Keller, Thierry (Fundación ONCE, 2013)
In an era where rehabilitation services are diminishing under the weight of the growing demands and fewer therapists, home-based telerehabilitation offers a way of increasing duration and intensity of post-stroke training. Novel systems that guide the therapist and patient in planning, executing, and assessing the training can reduce the burden on the healthcare system while maintaining or improving the quality of care. To achieve this effectively, a unified approach is needed that can address the diverse needs of the users and adequately assess the level of mobility deficits remotely. This document presents a methodology and prototype system for assessment and training adaptation within a telerehabilitation framework targeting home-based rehabilitation of the upper limbs after stroke. The framework uses 4 games for assessment of motor performance based on measures of range and control of movement. Assessment games include range of motion, range of force, control of motion, and control of force. The initial assessment games are used to tune the deficit-specific parameters in each successive game for assessment and training. Games are administered over the web-based TeleREHA platform through a novel arm rehabilitation device called the ArmAssist. An overview of the developments in each project is presented including the basic assessment parameters and a methodology for making patient-specific adaptation to game levels. Preliminary feedback from an ongoing usability evaluation is also presented and discussed.
Keywords: Discapacidad física y orgánica; Rehabilitación; Extremidades superiores; Nuevas tecnologías; Juegos; Movilidad; Medición; Resultados; Evaluación; Experiencias